Colonialism, postcolonialism and the liberal welfare state - Bhambra, Gurminder K.; Holmwood, John (Taylor & Francis, 2018)
This article addresses the colonial and racial origins of the welfare state with a particular emphasis on the liberal welfare state of the USA and UK. Both are understood in terms of the centrality of the commodified status of labour power expressing a logic of market relations. In contrast, we argue that with a proper understanding of the relations of capitalism and colonialism, the sale of labour power as a commodity already represents a movement away from the commodified form of labour represented by enslavement. European colonialism is integral to the development of welfare states and their forms of inclusion and exclusion which remain racialised through into the twenty-first century.